MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI PEMBELAJARAN DENGAN PETA KONSEP - Supratman Supratman (Khazanah Pendidikan, 2010)
This research was aimed at finding out the ability to solve mathematics problem through conceptual map learning. The other objective is to know both the constraint and support of this type of learning. The stages include instrumnet development, giving treatment, and administering the test. The analysis of this reasearch was done to give interpretation the ability to solve mathematics problem for both mathematics and wholistic problem solving. The significance test used was that of parametric statistics, namely t-test used to process the result of problem solving test. The finding was that the student’s ability of solving mathematics problem through the useof conceptual map learning improved significantly than that of conventional learning for both aspect of mathematics and wholistic problem solving. Key words: Conceptual map-learning, the ability to solve mathematics problem